2020
DOI: 10.26599/jnr.2020.9040009
|View full text |Cite
|
Sign up to set email alerts
|

Clinical neurorestorative cell therapies: Developmental process, current state and future prospective

Abstract: Clinical cell therapies (CTs) for neurological diseases and cellular damage have been explored for more than 2 decades. According to the United States Food and Drug Administration, there are 2 types of cell categories for therapy, namely stem cell-derived CT products and mature/functionally differentiated cell-derived CT products. However, regardless of the type of CT used, the majority of reports of clinical CTs from either small sample sizes based on single-center phase 1 or 2 unblinded trials or retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 252 publications
0
22
0
Order By: Relevance
“…Numerous therapeutic strategies for alleviating in ammation, scavenging reactive oxygen species, and promoting tissue regeneration have been developed for TBI recovery 32 . Of these, stem cell-based therapy provided an ideal therapeutic option for neurological disorders based on its ability to inhibit neuroin ammation and promote tissue reconstruction 33 . In the present study, we found that FbMSCs isolated from the frontal bone demonstrated some characteristics of NSCs, and were ectoderm-derived and could differentiate into different types of neurons (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous therapeutic strategies for alleviating in ammation, scavenging reactive oxygen species, and promoting tissue regeneration have been developed for TBI recovery 32 . Of these, stem cell-based therapy provided an ideal therapeutic option for neurological disorders based on its ability to inhibit neuroin ammation and promote tissue reconstruction 33 . In the present study, we found that FbMSCs isolated from the frontal bone demonstrated some characteristics of NSCs, and were ectoderm-derived and could differentiate into different types of neurons (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their multiple differentiate into multiple tissues such as bone, cartilage, adipose, and neuronal cells, they are immune-privileged and immunomodulatory 12 . MSC transplantation for TBI therapy has been investigated in animal models and clinical trials, showing signi cant improvements in neurological function 13 . Previous studies have revealed that neurorestoration and not neuro-replacement, contributes to MSC transplantation-induced TBI recovery 8 .…”
Section: Introductionmentioning
confidence: 99%
“…The BTB parallels the blood-brain barrier (BBB) and is comprised of vascular endothelial cells, basement membrane, and glioma cells. This structure can seriously impede the entry of drugs into the tumor microenvironment, resulting in poor drug efficacy and extremely unfavorable patient prognosis (59)(60)(61). Consequently, exploring lncRNAs that can regulate BTB permeability to promote chemotherapy and thus improve drug efficacy is one of the research directions for targeted glioma therapy.…”
Section: Lncrnas As Reliable Therapeutic Targets Treatment Strategies Involving Lncrnas As Regulators Modulating the Btbmentioning
confidence: 99%
“…The maximum daily dose is 1,000 μg. Moreover, it can be adjusted from 2 to 3 μg/h according to the clinical manifestation of the patient [58].…”
Section: Invasive Neuromodulation Therapymentioning
confidence: 99%